Identification of novel B-1 transitional progenitors by B-1 lymphocyte fate-mapping transgenic mouse model Bhlhe41dTomato-Cre - Li, Hui; Tang, Yangyang; Ren, Jinfeng; Bai, Ruixue; Hu, Lang; Jia, Wenyu; Cao, Yiwei; Hong, Li; Xu, Meizhen; Gao, Sijia; Shi, Yanbiao; Pan, Shuai; et al. (Frontiers in Immunology, 2022)
B-1 lymphocytes exhibit specialized roles in host defense against multiple pathogens. Despite CD19+CD93+B220lo/- B cells have been identified as B-1 progenitors, the definition for B-1 progenitors remain to be elucidated as CD19+CD93+B220+ B cells are capable to give rise to B-1 cells. Given that transcription factor Bhlhe41 is highly and preferentially expressed in B-1 cells and regulates B-1a cell development, we generated a transgenic mouse model, Bhlhe41dTomato-Cre, for fate mapping and functional analysis of B-1 cells. Bhlhe41dTomato-Cre mice efficiently traced Bhlhe41 expression, which was mainly restricted to B-1 cells in B cell lineage. We showed an efficient and specific Cre-mediated DNA recombination in adult B-1 cells and neonatal B-1 progenitors rather than B-2 cells by flow cytometric analysis of Bhlhe41dTomato-Cre/+Rosa26EYFP mice. Treatment of Bhlhe41dTomato-Cre/+Rosa26iDTR mice with diphtheria toxin revealed a robust efficacy of B-1 cell depletion. Interestingly, using Bhlhe41dTomato-Cre mice we demonstrated that neonatal B-1 progenitors (CD19+CD93+B220lo/-) expressed Bhlhe41 and were identical to well-defined transitional B-1a progenitors (CD19+CD93+B220lo/-CD5+), which only gave rise to peritoneal B-1a cells. Moreover, we identified a novel population of neonatal splenic CD19hidTomato+B220hiCD43loCD5lo B cells, which differentiated to peritoneal B-1a and B-1b cells. Bhlhe41 deficiency impaired the balance between CD19hidTomato+B220lo/-CD5hi and CD19hidTomato+B220hiCD5lo cells. Hence, we identified neonatal CD19hidTomato+B220hiCD43loCD5lo B cells as novel transitional B-1 progenitors. Bhlhe41dTomato-Cre/+ mouse can be used for fate mapping and functional studies of B-1 cells in host immune responses.